Reflections on captivity : a tapestry of stories by a Vietnam War POW - Halyburton, Porter (Naval Institute Press, 2022)
"On October 17, 1965, Navy LTJG Porter Halyburton was shot down over North Vietnam on his 76th mission and listed as killed in action. One-and-a-half years later he was found to be alive and a prisoner of war. Halyburton was held captive for more than seven years. Reflections on Captivity is a collection of fifty short stories about this young naval officer's experiences as a POW in North Vietnam"--